2008
DOI: 10.1021/nl801180c
|View full text |Cite
|
Sign up to set email alerts
|

Using Localized Surface Plasmon Resonances to Probe the Nanoscopic Origins of Adsorbate-Driven Ordering Transitions of Liquid Crystals in Contact with Chemically Functionalized Gold Nanodots

Abstract: We report that localized surface plasmon resonances (LSPRs) of gold nanodots immersed under liquid crystals (LCs) can be used to characterize adsorbate-induced ordering transitions of the LCs on the surfaces of the nanodots. The nanoscopic changes in ordering of the LCs, as measured by LSPR, were shown to give rise to macroscopic ordering transitions of the LCs that were observed by polarized light microscopy. The results reported herein suggest that (i) LCs may be useful for enhancing the sensitivity of LSPR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 42 publications
(96 reference statements)
1
40
0
Order By: Relevance
“…A second study has used surfaces decorated with gold nanoparticles that were functionalized with Cu 2+ ions 76. As described in Figure 4, this system is an interesting one because coordination interactions between the Cu 2+ and 5CB leads to local homeotropic ordering of the LC.…”
Section: Section 3: Colloidal Interactions Mediated By Lcsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second study has used surfaces decorated with gold nanoparticles that were functionalized with Cu 2+ ions 76. As described in Figure 4, this system is an interesting one because coordination interactions between the Cu 2+ and 5CB leads to local homeotropic ordering of the LC.…”
Section: Section 3: Colloidal Interactions Mediated By Lcsmentioning
confidence: 99%
“…These results suggest that cooperative ordering transitions involving nematic LCs can be used to amplify the changes in refractive index about nanoparticles and increase LPSR responses to binding events. 76…”
Section: Section 3: Colloidal Interactions Mediated By Lcsmentioning
confidence: 99%
“…Such systems have a potential for the development of new composite materials that can be used as chemical and biological sensors and novel types of electro-optic devices. In fact studies on plasmonic metal NPs dispersed in LCs have shown that the optical properties are quite sensitive to the presence of NPs [1,2]. Another type of LC-NP composite that has been extensively studied makes use of NPs of the ferroelectric materials BaTiO 3 and Sn 2 P 2 S 6 [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Various liquid crystal display (LCD) modes, such as vertical alignment (VA) [1][2][3][4][5][6][7][8][9][10][11][12], in-plane switching (IPS) [13], and fringe-field switching (FFS) [14][15][16][17], have been developed to improve the image quality of LCDs. The VA mode exhibits a high contrast ratio for normal viewing and can be fabricated simply without need for rubbing.…”
Section: Introductionmentioning
confidence: 99%
“…The VA mode exhibits a high contrast ratio for normal viewing and can be fabricated simply without need for rubbing. Although the viewing angle properties of the VA mode are inferior to the other modes, this has been overcome using multi-domain technology with protrusion (MVA) [1][2][3], patterned electrodes (PVA) [4][5][6], 4 Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%